In vitro evaluation of cytotoxic and apoptotic activities of ethanolic extract of sweet apricot kernel on PANC-1 pancreatic cancer cells. Issue 1 (29th September 2021) - Aamazadeh, Fatemeh; Barar, Jaleh; Rahbar Saadat, Yalda; Ostadrahimi, Alireza
Abstract : Purpose: This study aimed to evaluate the cytotoxic/apoptotic effects of sweet apricot kernel ethanolic extract (SAEE) on human cancerous PANC-1 and 293/KDR normal cells. Design/methodology/approach: The extract was prepared by maceration, and its chemical composition was analyzed by gas chromatography-mass spectrometry (GC-MS). The biological effects of SAEE on PANC-1 and 293/KDR cells were investigated using MTT (3–(4, 5-dimethylthiazole-2-yl)-2, 5-diphenyl tetrazolium bromide) assay, DAPI (4', 6-diamidino-2-phenylindole) and AnnexinV/propidium iodide (PI) staining. The expression of pro- and anti-apoptotic genes was evaluated by real-time quantitative polymerase chain reaction (real-time q-PCR) analysis. Findings: The SAEE showed the selective growth inhibitory activity against PANC-1 cells with an IC50 (the 50% inhibitory concentration) value of about 1 mg/mL at 72 h. Further investigations by DAPI staining and flow cytometry revealed nucleus fragmentation and elevation of apoptotic cells, respectively. Also, a significant decrease in B-cell lymphoma 2 (Bcl-2)/Bcl-2-associated x protein (Bax) ratio (0.41, p = 0.001) and the up-regulation of caspase-3 expression (1.5 fold, p = 0.002) indicated the induction of apoptosis in PANC-1 cells but not in 293/KDR non-cancerous cells. These results suggest that SAEE could induce apoptosis in cancer cells via a mitochondrial dependent pathway. Furthermore, GC-MS analysis showed that the SAEE is rich in γ-sitosterol and γ-tocopherol. Overall, the findings suggest that because of the selective impacts of SAEE on PANC-1 cells, it can be considered as a supportive care in adjuvant therapy for pancreatic cancer. However, the potent anticancer effects of main components of SAEE and its clinical value as an antitumor drug should be further investigated. Research limitations/implications: Considerable limitations of this study were that the related mechanisms of selective impacts of SAEE on cancerous and normal cells and potent cytotoxic/apoptotic effects of γ-sitosterol and γ-tocopherol as major components of SAEE were not investigated. Originality/value: Recently, a growing interest has been dedicated to plant-based natural products. Sweet apricot kernel exerts a number of pharmacological activities; however, the anticancer effect, related mechanisms and its active compounds were rarely investigated. In this study, the authors aimed to evaluate the cytotoxic/apoptotic effects of SAEE on human cancerous PANC-1 and 293/KDR normal cells.